Behemoth - Westerfeld, Scott; Thompson, Keith, 1982- (New York : Simon Pulse, 2010)
Continues the story of Austrian Prince Alek who, in an alternate 1914 Europe, eludes the Germans by traveling in the Leviathan to Constantinople, where he faces a whole new kind of genetically-engineered warships.
Sequel to: Leviathan.
810
Keywords: Animals, Mythical -- Juvenile fiction; Princes -- Juvenile fiction; Genetic engineering -- Juvenile fiction; War fiction; Alternative histories (Fiction).; Steampunk fiction; Science fiction